Pesantren and the Khilafah Discourse: Responses of Kiai in South Sumatra on Religion–State Relations - Izomiddin, Izomiddin; Jamil, Syahril; Hadi, Abdul; Torik, Muhammad (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine the responses of pesantren communities in South Sumatra to the discourse of khilafah, particularly how kiai and santri interpret exclusive and inclusive Islamic texts in relation to religion–state dynamics. The research employed a qualitative method with a critical hermeneutic approach, combining in-depth interviews, participatory observation, and documentation studies in five pesantren across three districts. The findings reveal that the pesantren communities do not perceive the khilafah merely as a political project, but as a discourse negotiated through da‘wah, education, and religious authority. Three major patterns of response were identified: (1) support for the nation-state while internalising Islamic values through da‘wah and education; (2) reflective acceptance of the khilafah as an ideal, but with contextual consideration for Indonesia’s pluralistic reality; and (3) normative rejection of both the nation-state and khilafah based on critical views of political failures. These responses demonstrate the active role of pesantren in shaping Islamic discourse, promoting moderation, and safeguarding national unity. The study concludes that pesantren function not only as educational institutions but also as centres of da‘wah and socio-political negotiation that adaptively respond to transnational Islamic ideologies in contemporary Indonesia.